PENYUSUNAN E-BOOKLET BURUNG KICAU YANG DILINDUNGI DI PASTY SEBAGAI SUMBER BELAJAR BIOLOGI - Maya Pratiwi; Arief Abdillah Nurusman; Destri Ratna Ma’rifah; Dwi Nugroho; Novi Febrianti (Bioilmi: Jurnal Pendidikan, 2022)
This study aims to determine the quality of the protected chirping bird E-booklet at the Yogyakarta Various Animal and Ornamental Plants Market (PASTY) as a learning resource for class X biology based on material experts, media experts, and biology teachers. In this study, the preparation of an E-booklet adapted from a 4D model (define, design, develop, and disseminate) is limited to the develop stage. The quality assessment e-booklet uses a questionnaire method. Likert scale questionnaire (4 scales) was used to validate the product. Product validation was carried out by media experts, namely Biology Education lecturer at Ahmad Dahlan University, material expert namely ornithologist from the Science for Endangered and Trafficked Foundation (SCENTS), and class X Biology teacher at SMA Negeri 11 Yogyakarta. Data from the assessment questionnaire was then analyzed descriptively to determine the quality of the E-booklet. The results of the assessments from material experts, media experts, and Biology teachers showed that the quality of the compiled E-booklets was in the very good category.